Time–Frequency Analysis of Muscle Activation Patterns during the Instep Kick in Elite and Amateur Soccer Players - Jiazhong Zhu; Diwei Chen; Dongxu Wang; Zhanyi Zhou; Yang Song; Xuanzhen Cen; Gusztáv Fekete; Monèm Jemni; Huw Wiltshire; Julien Steven Baker; Yaodong Gu; Dong Sun (Journal of Sports Science and Medicine, 2026)
The instep kick is a frequently performed, high-load soccer skill that requires precise intermuscular coordination around ball contact. This study compared time-frequency activation patterns between elite and amateur male soccer players across two kicking phases and identified the key time windows and dominant muscle contributions. Surface electromyography was recorded from seven muscles of the kicking leg in 15 elite and 15 amateur players: rectus femoris, vastus medialis, vastus lateralis, biceps femoris, tibialis anterior, medial gastrocnemius, and lateral gastrocnemius. The instep kick was divided into Phase 1, from maximum hip extension to ball contact, and Phase 2, from post-contact follow-through to maximum hip flexion. Morlet wavelet analysis was used to generate time-frequency intensity maps. Global principal component analysis was then performed to extract PC1 to PC6, and between-group differences in PC score trajectories were assessed using SPM1D independent-samples t tests, with significance evaluated under a Bonferroni adjusted threshold for the 12 PC phase comparisons. In Phase 1, PC3 showed a significant between-group difference at 54-75% of the normalized time (peak t = 7.62, p < 0.001, Hedges’ g = 2.96), with higher scores in the elite group. In Phase 2, PC1 differed significantly between groups at 60-70% of the normalized time (peak t = -9.88, p < 0.001, Hedges’ g = -2.03), with higher scores in the amateur group. Elite players showed a more temporally focused pre-contact activation pattern centered on mid-frequency components of the biceps femoris, whereas amateur players showed greater reliance on higher-frequency components of the medial gastrocnemius during the post-contact follow-through. These findings suggest that skill-level differences are expressed as phase-specific redistribution of muscle and frequency-band activity within critical time windows, rather than as a simple global difference in activation magnitude.